Pengaruh Beda Potensial dan Waktu Kontak terhadap Penurunan Kadar COD dan TSS pada Limbah Batik menggunakan Metode Elektrokagulasi - Devy, Belinda Liana; A. R., Haryanto (Talenta Publisher (Universitas Sumatera Utara), 2021)
Batik is one of Indonesia's original cultural heritage that must be preserved. However, the resulting liquid waste has a negative impact on the environment because it contains high levels of phosphate, surfactant, TSS, TDS, turbidity, BOD5 and COD contaminants. An effective method for dealing with batik waste is electrocoagulation, which is coagulation in the presence of an electric current using electrodes. This study treats batik waste by electrocoagulation using aluminum electrodes, which are operated at a current of 5 Ampere, electrode distance is 2 cm, electrode thickness is 0.1 cm, electrode cross-sectional area is 7x10 cm with a waste volume of 500 mL. The effect of potential difference treatment (3 volts, 4.5 volts, 7.5 volts, 9 volts, and 12 volts) and contact time (15 minutes, 20 minutes, 25 minutes, 30 minutes, and 35 minutes) on changes in COD and TSS levels were studied. Optimal conditions were obtained at a potential difference of 12 volts for 35 minutes with a COD reduction efficiency of 84.84% and 91% for TSS.